STRATEGI KOMUNIKASI ORGANISASI DALAM MENGOPTIMALKAN BUDAYA MUTU DI KANTOR BANK BPD BALI CABANG MATARAM - Indiana, Ni Made; I Dewa Ayu Hendrawathy Putri; I Nyoman Subagia (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
This study examines organizational communication at the Mataram Branch of Bank BPD Bali, focusing on reinforcing the bank's established CINTA culture, which emphasizes Competence, Integrity, Teamwork, and Customer Awareness. The research addresses three main questions: 1) How is the organizational communication process structured to enhance the quality culture at the Mataram branch? 2) What communication strategies are used to strengthen this culture? 3) How do branch leaders manage obstacles in executing these strategies? Using a qualitative descriptive approach, the study reveals that the Mataram branch operates within a complex open system, relying on interdependent relationships within and outside the organization. This system fosters interpersonal communication among team members to exchange information and share perspectives. The strategies employed effectively capitalize on internal strengths and external opportunities while mitigating internal and external challenges. The success of these efforts is reflected in the partners' acceptance of the CINTA culture, allowing the branch to sustain economic operations while bridging internal differences within the organization and the cultural background of the West Nusa Tenggara region.